Somatotrophic axis genes on growth traits in a bovine F2 population - Silva, Marcos Vinicius Gualberto Barbosa da; Martinez, Mário Luiz; Machado, Marco Antonio; Nascimento, Carlos Souza do; Campos, Ana Lúcia; Guimarães, Marta Fonseca Martins; Azevedo, Ana Luisa Sousa; Moita, Antônia Kécya França; Lui, Jeffrey Frederico (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to evaluate the association between polymorphisms of bGH, IGF-1 and PIT-1 genes with weight and weight gain traits in a bovine F2 population derived from Holstein x Gyr crosses, using the PCR-RFLP technique. Allelic frequencies A and B of PIT-1 gene and AA, AB, and BB genotypes were similar between parental populations but different from F1 and F2 crossed populations. For the bGH gene, Holstein animals showed allelic frequency of 100% for E allele, while Gyr animals showed allelic frequency of 92% for F allele, resulting in high frequency of heterozygous animals in F1 and F2 populations. For the IGF-1 gene, all Holstein were heterozygous (AB) and most Gyr were homozygous (AA), resulting in a high frequency of A allele in F1 and F2 populations. Significant associations were found between PIT-1 allele A with traits weight at 60, 205 and 365 days and weight gain from birth to 60 days. For IGF-1, significant association was found between A allele and birth weight. For bGH gene, significant associations were found between E allele and 365 days weight and weight gain from birth to 60 days. The selected alleles could be used as markers in animal breeding for these traits.